Neglection in Family as Reason for Divorce during The Covid-19 Pandemic In The Siak Religious Court [Penelantaran Rumah Tangga Sebagai Bentuk Kekerasan dalam Rumah Tangga sebagai Alasan Perceraian di Masa Pandemi Covid-19: Studi Kasus Pengadilan Agama Siak] - Yusnanik Bakhtiar (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2020)
Abstract: Divorce can happen to any household that is experiencing problems. Many factors lead to divorce, among which the most dominant are disputes and continuous quarrels, leaving one party behind, economic factors. During this Corona Pandemic, of course, it will affect the divorce rate at the Siak Religious Court. The effects of this corona pandemic can cause divorce rates to increase or vice versa tend to decrease. This type of research is empirical research that uses empirical juridical research with a sociological juridical approach. This research is located in the Siak Religious Court. From the results of the research that the author did, data on the number of divorces that entered the Siak Religious Court in 2019 were 581 cases consisting of 175 cases of talak divorce and 406 sued divorce cases. Meanwhile, from 2020 to October there was a downward trend in divorce cases as many as 459 cases consisting of 131 divorce cases and 328 lawsuits. So it can be concluded that the corona pandemic has no impact on divorce cases in the Siak Religious Court. The cause of the divorce is the background of 78.50% of continuous disputes and quarrels, leaving one of the parties 16.20% and economic factors as much as 3.55%. Regarding divorce itself, it is regulated in Law no. 1 of 1974 concerning Marriage, Government Regulation no. 9 of 1975 concerning the Implementation of Law No. 1 of 1974 concerning Marriage, and Presidential Instruction No. 1 of 1991 concerning the Compilation of Islamic Law. Abstrak: Perceraian bisa saja terjadi pada setiap rumah tangga yang mengalami permasalahan. Banyak faktor yang menyebabkan perceraian, di antaranya yang menjadi paling dominan adalah perselisihan dan pertengkaran terus menerus, meninggalkan salah satu pihak, faktor ekonomi. Pada saat Pandemi Korona ini tentu saja akan mempengaruhi angka perceraian di Pengadilan Agama Siak. Efek pandemi korona ini bisa menyebabkan angka perceraian meningkat atau sebaliknya cenderung menurun. Jenis penelitian ini adalah penelitian empiris yang menggunakan jenis penelitian yuridis empiris dengan metode pendekatan yuridis sosiologis. Penelitian ini berlokasi di Pengadilan Agama Siak. Dari hasil penelitian yang penulis lakukan maka diperoleh data angka perceraian masuk ke Pengadilan Agama Siak pada tahun 2019 sebanyak 581 kasus yang terdiri dari cerai talak 175 kasus dan cerai gugat sebanyak 406 kasus. Sedangkan pada tahun 2020 sampai bulan Oktober terjadi kecenderungan penurunan kasus perceraian sebanyak 459 kasus yang terdiri dari cerai talak 131 kasus dan cerai gugat 328 kasus. Sehingga dapat disimpulkan bahwa pandemi korona tidak berdampak kepada kasus perceraian yang ada di Pengadilan Agama Siak. Penyebab terjadinya perceraian tersebut dilatar belakangi oleh perselisihan dan pertengkaran terus menerus sebanyak 78,50 %, meninggalkan salah satu pihak 16,20 % dan faktor ekonomi sebanyak 3,55 %. Mengenai perceraian ini sendiri diatur di dalam Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan, Peraturan Pemerintah Nomor 9 Tahun 1975 tentang Pelaksanaan Undang- Undang Nomor 1 Tahun 1974 tentang Perkawinan, dan Inpres Nomor 1 Tahun 1991 tentang Kompilasi Hukum Islam.